Hydrogeological and hydrogeochemical characterization of the unconfined aquifer in the fluvio-eolian plain of Cordoba (Argentina) - Bécher Quinodóz, Fátima Noelia (2019)
The studied area, a vast plain located in the South of Córdoba (Argentina), presents a relief resulting from the juxtaposition of an eolian and a fluvial system. The objective of this work was to characterize the unconfined aquifer from a dynamic and a geochemical point of view, establishing relationships with lithological and geomorphological features and validating with statistical multivariate analysis (Q mode) of the geochemical data. The unconfined aquifer presents variable hydraulic gradients and groundwater velocity, both conditioned by the local relief and lithology. The aquifer showed a varied spatial geochemical pattern with fresh to salty water (0.4–10.0 g/L) and sodium bicarbonate to sodium chloride geochemical types, in some places of mixed anionic type. The statistical analysis showed two groups: Group 1 links salty-brackish groundwater of sulfate and chloride type with longitudinal dunes and lowlands with locally outcropping water. It represents evolved groundwater coming from intermediate and regional flows. Group 2 links fresh groundwater of bicarbonate type with active dunes and paleochannels. In these sites, where coarser sediments prevail, local groundwater flow cells develop as a result of recent recharge, leading to greater groundwater velocity and decreasing the transference of ions to solution. These results allow us to identify the most promising areas for freshwater abstraction.